A framework for measuring the levels of maturity of lean initiatives in healthcare organisations - Diaz, Rodrigo (2010)
Lean healthcare are getting many adepts nowadays in literature as in the healthcare organisations. This is because there are many successful cases in manufacturing and in the services sector that have adopt lean as a tool and methodology to reduce cost, improve quality and increase performance. But implementing lean is not as easy as it looks, and requires to follow a structured methodology, which has different variants to consider to achieve a level of maturity and sustainability, which is the base of lean. Many companies try to apply lean tools, methods and techniques, and there is too much information of different initiatives, but very little in literature about how to move from a current state of implementation and see if the efforts are in a right direction. To help healthcare organisation that decide to adopt the use of lean at any level, it was created a framework named Lean Healthcare Framework to measure the level of maturity of the usage of lean. This framework was created from two models of lean manufacturing and adapted/adjusted to lean healthcare. The Lean Healthcare Framework provide to the healthcare organisations an analysis of their lean initiatives to identify in which level of maturity their initiatives are located and secondly, it helps them to benchmark their initiatives with the best of class, and give them a roadmap to create a strategy to move into the next level of maturity of usage of lean initiatives.